Seasonal malaria attack rates in infants and young children in northern Ghana. - Baird, J; Owusu Agyei, S; Utz, G; Koram, K; Barcus, M; Jones, T; Fryauff, D; Binka, F; Hoffman, S; Nkrumah, F (2002)
The incidence density of infection and disease caused by Plasmodium falciparum in children aged six to 24 months living in the holoendemic Sahel of northern Ghana was measured during the wet and dry seasons of 1996 and 1997. At the beginning of each season, a cohort composed of 259 and 277 randomly selected children received supervised curative therapy with quinine and Fansidar and primaquine for those with normal glucose-6-phosphate dehydrogenase activity. The 20 weeks of post-therapy follow-up consisted of three home visits weekly and examination of Giemsa-stained blood films once every two weeks. Blood films were also taken from children brought to clinic with illness. The incidence density of parasitemia after radical cure was 4.7 infections/person-year during the dry season and 7.1 during the wet season (relative risk = 1.51, 95% confidence interval [CI] = 1.25-1.81; P = 0.00001). Although the mean parasitemia count at time of reinfection in the dry season (3,310/microl) roughly equaled that in the wet season (3,056/microl; P = 0.737), the risk ratio for parasitemia > 20,000/microl during the wet season was 1.71 (95% CI = 1.2-2.4; P = 0.0025). The risk ratio for parasitemia > 20,000/microl with fever during the wet season was 2.45 (95% CI = 1.5-4.1; P = 0.0002). The risk ratio for anemia (hemoglobin < 8 g/dl) at first post-radical cure parasitemia showed no difference between seasons (1.0; 95% CI = 0.73-1.4; P = 0.9915). We did not see seasonal differences in anemia known to exist in this region, probably because the longitudinal cohort design using first parasitemia as an end point prevented the subjects from developing the repeated or chronic infections required for anemia induction. These findings bear upon the design of malaria drug and vaccine trials in holoendemic areas.